The Concept of Tolerance in the Qur'an as A Basis for Strengthening Islamic Education - Lailatul Mukaromah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to determine the values of tolerance in the Qur'an as a reinforcement for the world of education.  The method used in the research is library research by collecting data from literature and information sources, be it books, journals, e-books, articles, theses, internet and other literature sources related to related research.  Tolerance is an attitude of mutual respect and appreciation and does not restrict the freedom of others to do something.  This is evidenced in Surah al Baqarah verse 256 and Surah Ar Rum verse 22 which contain the value of tolerance, namely freedom of religion and respect for differences.  The form of strengthening the verse's education is freedom of thought, respect and respect for differences even though they have the same potential.